A Microbial Feed Additive Abates Intestinal Inflammation in Atlantic Salmon - Vasanth, Ghana; Kiron, Viswanath; Kulkarni, Amod; Dahle, Dalia; Lokesh, Jep; Kitani, Yoichiro (Frontiers in Immunology, 2015)
The efficacy of a microbial feed additive (Bactocell®) in countering intestinal inflammation in Atlantic salmon was examined in this study. Fish were fed either the additive-coated feed (probiotic) or feed without it (control). After an initial 3-week feeding, an inflammatory condition was induced by anally intubating all the fish with oxazolone. The fish were offered the feeds for 3 more weeks. Distal intestine from the groups was obtained at 4, 24 h, and 3 weeks, after oxazolone treatment. Inflammatory responses were prominent in both groups at 24 h, documented by changes in intestinal micromorphology, expression of inflammation-related genes and intestinal proteome. The control group was characterized by oedema, widening of intestinal villi and lamina propria, infiltration of granulocytes and lymphocytes, and higher expression of genes related to inflammatory responses, mul1b, il1b, tnfa, ifng, compared to the probiotic group or other time points of the control group. Further, the protein expression in the probiotic group at 24 h after inducing inflammation revealed 5 differentially regulated proteins - Calr, Psma5, Trp1, Ctsb and Naga. At 3 weeks after intubation, the inflammatory responses subsided in the probiotic group. The findings provide evidence that the microbial additive contributes to intestinal homeostasis in Atlantic salmon.